The first phylogenetic study of Mesembrinellidae (Diptera: Oestroidea) based on molecular data: clades and congruence with morphological characters (2017)
ABSTRACT: The Mesembrinellidae (Diptera: Oestroidea) comprise a small group of strictly Neotropical calyptrate flies, with 36 described species. The group has often been treated as a subfamily of Calliphoridae, but there is growing evidence that it corresponds to a distinct Oestroidea lineage. Internal relationships have so far been addressed based only on morphology, with results lacking resolution and support. This is the first molecular phylogeny for the group, which is based on the analyses of 80 terminal taxa (22 mesembrinellid and 28 outgroup species) and 5 molecular markers (ITS2, 28S, COI, COII and 16S). Maximum-parsimony, max- imum-likelihood and Bayesian inference methods were used, the latter two with partitioning strategies considering codon position and secondary structure information. Results corroborate the Mesembrinellidae as a monophyletic lineage inside Oestroidea. Three clades were consistently recovered: (1) (Laneella + Mesembrinella patriciae); (2) (Mesembrinella (excluding M. patriciae) + Eumesembrinella); and (3) (Huascaromusca + Giovanella). Re-examination of the female reproductive tract of M. pa- triciae revealed a Laneela-type spermatheca, which corroborates the position of the species recovered in the molecular phylogenetic analyses. Mesembrinella and Huascaromusca are in all cases paraphyletic with regards to Eumesembrinella and Giovanella, respectively. These latter two genera should, thus, be seen as subjective junior synonyms.